The Influence of Communication, Share Value, and Opportunistic Behavior Control On Customer Loyalty in Internet Banking - Dian Purnamasari; Nurul Aini; Joko Suyono (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: This paper aims to analyze the correspondency of multiple variables such as communication, share value, opportunistic behavior control, trust, and loyalty in the case of internet banking. The analysis is mediated by customer’s trust. Design/methodology/approach: The method used is statistic-descriptive, followed by purposive sampling as the data collection method. Design used is cross sectional. Findings: Among the hypotheses proposed, there are 4 that show positive results. Those include share value that has positive impact on the customer’s trust on Bank Jatim, internet banking customer’s loyalty on Bank Jatim, and customer’s loyalty in using the Bank’s internet banking mediated through trust. Research limitations/implications: The sample includes 135 respondents from Bank Jatim Surabaya that use internet banking. Practical implications: Among the hypotheses proposed, 2 out of 6 are not acceptable because the statistics show inadequate percentage. Paper type: This paper can be categorized as a case study.